Des désastres écologiques au rêve panafricain d'une Grande Muraille verte. (1st December 2020) - Crosta, Suzanne
Since the late twentieth century, African filmmakers have devoted themselves with tireless dedication and activism to environmental challenges that continue to alarm, even globally. Their lands are endangered, and their communities are severely affected in their living environment. There are major challenges, ever more urgent, about their ecosystems, but also about the neighbouring geographies and finally about the planet in general. Using a body of documentaries concerned with ecosystems on the continent, this study examines African filmmakers' perspectives on ecosystem degradation in various African contexts while highlighting the ethics and aesthetics of their practices confronting the representation of a seemingly dystopian world. In response to the alarming discourses and desolate visions, this article underscores the filmmakers' response to urgent ecological needs, and examines their activism in the search for green solutions in Africa.